Potent efficacy of metronomic topotecan and pazopanib combination therapy in preclinical models of primary or late stage metastatic triple-negative breast cancer - Di Desidero, Teresa (Oncotarget, 2015)
Metronomic chemotherapy has shown promising activity in numerous preclinical studies and also some phase II clinical studies involving various tumor types, and is currently undergoing phase III trial evaluation. Triple-negative breast cancer (TNBC) is an aggressive histological subtype with limited treatment options and very poor prognosis following progression after standard chemotherapeutic regimens. Herein, we evaluated the potential therapeutic impact and molecular mechanisms of topotecan administered in a continuous low-dose metronomic (LDM) manner, alone or in concurrent combination with pazopanib, an antiangiogenic tyrosine kinase inhibitor (TKI), in a triple-negative, primary and metastatic breast cancer orthotopic model; potential molecular mechanisms of efficacy were also studied, especially the impact of hypoxic conditions. The combination of metronomic topotecan and pazopanib significantly enhanced antitumor activity compared to monotherapy with either drug and prolonged survival, even in the advanced metastatic survival setting, with a marked decrease in tumor vascularity, proliferative index, and the induction of apoptosis. Significant changes in tumor angiogenesis, cancer cell proliferation, apoptosis, HIF1α levels, HIF-1 target genes and ABCG2 were found both in vitro and in tumor tissue. Notably, the pazopanib and metronomic topotecan combination treatment inhibited expression of HIF1α and ABCG2 genes in cells grown under hypoxic conditions, and this was associated with an increased intracellular concentration of the active form of topotecan. Our results suggest a potential novel therapeutic option for the treatment of metastatic triple-negative breast cancer patients.